Synthesis Cartography as Instrument for Evaluating Potential of Linear Erosive Dynamics in Cuesta Domain - Stefanuto, Estêvão Botura [UNESP]; Lupinacci, Cenira Maria [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2021)
Soil erosion by water is estimated at an annual cost of billions of dollars to global GDP. To study this problem, we consider that evaluating the spatial disposition of erosive phenomena, as well as the interaction of variables that influence their dynamics, constitutes an essential prerogative. Thus, the aim of this article is to present methodological procedures adopted for the development of synthesis maps in order to identify the potential of the land to advance linear erosion. The variables used to analyze the erosive potential were relief morphometry, soil physical characteristics and land use. Principles of map algebra were used, with emphasis on the weighted overlay of the variables, starting from different influences for each of these and different techniques for the establishment of weights for the classes of each variable. The cartographic documents created were evaluated from the comparison of these with experimental field data and mapping of linear features. It was found that the best answers occurred when an equitable influence was considered for the physical and land use variables, demonstrating that erosive features are the result of the interaction between human action and the natural characteristics of the terrain. It was also possible to conclude that the technical procedures that allow us to obtain good results to assess the potential for the development of gullies, don't respond adequately to rill erosion and ravines, and there is a need for adaptations. It’s considered that the maps elaborated, as well as the methodological procedures developed, support for the analysis of linear erosive dynamics in Cuesta sectors, for it was possible to obtain cartographic products that presented good spatial correspondence with the erosive features recorded in the field.
A Cartografia de Síntese como Instrumento para a Avaliação do Potencial da Dinâmica Erosiva Linear em Domínio de Cuesta
Keywords: Cartography; Erosion; Erosive diagnosis; Erosive evolution